Image analysis derived ploidy and proliferation indices in soft tissue sarcomas: comparison with clinical outcome. Issue 5 (May 1994) - Michie, B A; Black, C; Reid, R P; Barrett, A; Hamblen, D L
Abstract : AIMS--To compare prognostic information obtained by image analysis cytometry of paraffin wax embedded soft tissue sarcomas with conventional assessment. METHODS--A CAS 200 image analyser was used to determine DNA content of Feulgen stained cytology preparations and tissue sections and to quantify immunostaining by Ki67 and PC10 antibodies. A mitotic count in 50 high power fields was undertaken and histological grade assigned by the Trojani system. Clinical details including follow up and outcome were obtained by case note review. The Kruskal-Wallis one way analysis test, Spearman rho significance test, Kaplan-Meier method, and log-rank test were applied in statistical analysis. RESULTS--Ploidy status, DNA index, 2.5c exceeding rate, 5c exceeding rate, mitotic count and Trojani grade all correlated significantly with clinical outcome. The relation between Ki67 index and outcome did not reach significance. The PC10 index and outcome were not related. Only 2.5c exceeding rate, 5c exceeding rate, and mitotic count correlated significantly with Trojani grade. CONCLUSIONS--DNA content determination of soft tissue sarcomas by image analysis provides quantifiable information of benefit in prediction of outcome. Larger series are required to determine the independent value of ploidy. In this study quantification of anti-Ki67 and anti-PC10 immunostaining was not of prognostic benefit) by contrast with mitotic count and Trojani grade.